2017
DOI: 10.1371/journal.pone.0170784
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of MALDI-TOF MS as a Diagnostic Tool for the Identification of Streptococcus Species Recovered from Clinical Specimens of Pigs

Abstract: The application of MALDI-TOF MS for identifying streptococcal isolates recovered from clinical specimens of diseased pigs was evaluated. For this proposal, the MALDI BDAL Database (Bruker Daltoniks, Germany) was supplemented with the main spectrum profiles (MSP) of the reference strains of S. porci, S. porcorum and S. plurextorum associated with pneumonia and septicemia. Although these three species showed similar MALDI profiles, several peaks were recognized that can be useful for their differentiation: S. po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
1
21
0
3
Order By: Relevance
“…Further, the MALTI-TOF-MS has also precisely confirmed that the isolate NBMKU12 belongs to the GAS. Previously, GAS clinical isolates have been identified by MALTI-TOF-MS ( Carbonnelle et al, 2011 ; Peârez-Sancho et al, 2017 ), and also group B Streptococcus (GBS) ( Binghuai et al, 2014 ; Singhai et al, 2015 ). The NBMKU12 was isolated from a male patient with a UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the MALTI-TOF-MS has also precisely confirmed that the isolate NBMKU12 belongs to the GAS. Previously, GAS clinical isolates have been identified by MALTI-TOF-MS ( Carbonnelle et al, 2011 ; Peârez-Sancho et al, 2017 ), and also group B Streptococcus (GBS) ( Binghuai et al, 2014 ; Singhai et al, 2015 ). The NBMKU12 was isolated from a male patient with a UTI.…”
Section: Discussionmentioning
confidence: 99%
“…The MALDI-TOF MS approach has been adopted as a routine diagnostic tool for human medicine [11] and has also been widely evaluated for its ability to differentiate bacterial species of veterinary and public health importance. For example, S. equi at the subspecies level [8], Streptococcus species isolated from diseased pigs [12], pathogenic Gram-negative bacteria in seafood [13] and Aeromonas species found in a drinking water system [14] have been assessed. In fish, MALDI-TOF was evaluated for the rapid identification of Gram-positive bacterial pathogens, including S. agalactiae, Lactococcus garvieae, S. iniae, and S. dysgalactiae isolated from Nile tilapia [15] and S. iniae isolated from the olive flounder Paralichthys olivaceus [16].…”
Section: Introductionmentioning
confidence: 99%
“…All clinical isolates were re‐identified against the ChMDB and the results obtained are shown in Table . Identification based exclusively in the first identification score provided by Biotyper is not the best approach for an accurate identification (Pérez‐Sancho et al., ). For this reason, in this study the consistency of MALDI‐TOF identification results was evaluated considering the two best identification matches provided by MALDI Biotyper ChMDB database (consistence identification categories A–D, Table ).…”
Section: Identification Results Of the 26 Fish Clinical Isolates Of Cmentioning
confidence: 99%